If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = -10 + -3n Solving 11 = -10 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 11 + 3n = -10 + -3n + 3n Combine like terms: -3n + 3n = 0 11 + 3n = -10 + 0 11 + 3n = -10 Add '-11' to each side of the equation. 11 + -11 + 3n = -10 + -11 Combine like terms: 11 + -11 = 0 0 + 3n = -10 + -11 3n = -10 + -11 Combine like terms: -10 + -11 = -21 3n = -21 Divide each side by '3'. n = -7 Simplifying n = -7
| 25x+20=145 | | 9+4x=5x+7 | | 17=6x+5 | | 2x=2x-13 | | -3=2k+9 | | 7x^2+19x=6 | | 27=-(n-9) | | 8(-4+r)=-16 | | 1=(m-3)-6m^2 | | -2p+8=5-(7p+3) | | -4=-(x+2) | | 4x^2+20x+9y^2-18y-2=0 | | 4x+13-[2x-(4x-12)-5]=2x-12 | | -14x+16=-35+11 | | g/6=20 | | 4+7n=20-3n | | X^2-99x-100=0 | | 5x+12=3x+30 | | -4p-2=42 | | 3(4j+12)=4(4j-12) | | 10(m-7)=110 | | 10(6+x)=150 | | 2(m+12)=7(m-8) | | 10(N-5)=-80 | | 6(3v-7)=3(4v+8) | | 1=-6+7k | | -2+14=0 | | -81=-9(-8+n) | | 3(6+2r)=8r-20 | | 3x+4=4x+3 | | 8t=20t-20 | | -(5y-6)+4(3+5y)y=2 |